A 3D oriented CuS/Cu2O/Cu nanowire photocathode. Issue 11 (19th February 2021) - He, Xuefeng; Chen, Xin; Chen, Rong; Zhu, Xun; Liao, Qiang; Ye, Dingding; Yu, Youxu; Zhang, Wei; Li, Jinwang
Abstract : The novelty of the work: a 3D oriented CuS/Cu2 O/Cu nanowire photocathode on copper foam toward the oxygen reduction reaction for a photocatalytic fuel cell. Abstract : In the present study, we present a 3D oriented CuS/Cu2 O/Cu nanowire photocathode grown on copper foam. This newly developed photocathode can effectively enhance the separation of electron–hole pairs and anti-photocorrosion as a result of the nanowire structure and bandgap gradient. In the meantime, it can provide more active sites and promote light utilization due to the vigorous porous structure and proper pore size. Experimental results confirmed the improved photoelectrochemical activity of the proposed photocathode as compared to the planar photocathode with CuS/Cu2 O/Cu nanowires. The in-cell performance measurements of a dual-photoelectrode photocatalytic fuel cell with the proposed photocathode also demonstrated the enhancement of the cell performance by the proposed photocathode, presenting about 88% improvement in the maximum power density. The 3D oriented CuS/Cu2 O/Cu nanowire photocathode represents a new route for the development of high-performance photocathodes, which can also be applied in other photoelectrochemical systems.